Reubicación y expectativas de modernidad: el caso de las familias campesinas de Yanacona y el proyecto Aeropuerto Internacional de Chinchero (Cusco) - López Aguilar, Marcos (Pontificia Universidad Católica del Perú. Fondo Editorial, 2019)
In December 2012, the Regional Government of Cusco expropriated lands owned by the rural community of Yanacona in order to allow the construction of the International Airport at Chinchero (Cusco). In addition to the payment of economic compensation, it undertook to relocate the population affected by the expropriation process. The article focuses on analyzing the resettlement process of the affected population and their expectations of modernity. The analysis shows that Regional Government did not ensure the mitigation of negative impacts of an involuntary resettlement process.Indeed, it was limited to financial compensation for the houses that the affected families would lose. Consequently, Regional Government did not ensure the reduction of the negative impact generated by a relocation. This was possible mainly due to the community’s expectations of modernity associated with the project.

En diciembre de 2012, el Gobierno Regional del Cusco expropió los terrenos de la comunidad campesina de Yanacona para la ejecución del Aeropuerto Internacional Chinchero-Cusco. Además del pago de una compensación económica, se comprometió a encargarse del proceso de reubicación. El artículo analiza el proceso de «reubicación» de la población afectada y sus expectativas de modernidad. El análisis muestra que el Gobierno regional no realizó propiamente un proceso reubicación involuntaria: se limitó a indemnizar a las familias afectadas por sus viviendas. Sin embargo, la compensación económica no aseguró una reducción de los impactos negativos provocados por la reubicación. Esto fue posible, principalmente, por las expectativas de modernidad de la comunidad asociadas al proyecto.
Resettlement and expectations of modernity: the case of peasant families of Yanacona and the Chinchero International Airport (Cusco)
Keywords: Reasentamiento involuntario; Tierras; Comunidades campesinas; Aeropuerto; Cusco; https://purl.org/pe-repo/ocde/ford#5.04.00